Networked Forces in Stability Operations 101st Airborne Division, 3/2 and 1/25 Stryker Brigades in Northern Iraq - Gonzales, Daniel (RAND Corporation, 2007)
Compares three units that conducted stability operations in the same area in northern Iraq-the 101st Airborne Division (which had only limited digital communications), the 3/2 Stryker brigade combat team (SBCT), and the 1/25 SBCT (both equipped with digital networks) and finds that leadership, training, and tactics and procedures are just as important as networking capabilities for improving mission effectiveness in stability operations.